Passing the USMLE Clinical Knowledge - Abdel-Halim, Ahmad Wagih. (Springer US, 2009)
With the pressure every medical student faces in preparing for the USMLE, time is of the essence when studying for the exam. Passing the USMLE: Clinical Knowledge is written with a tight focus on high yield information presented in simple text and bulleted lists for maximum retention. This book distills the vast ocean of medical science to the most pertinent stream of information necessary to successfully pass this rigorous examination. Organized by specialty, this book covers crucial topics in internal medicine, dermatology, obstetrics, gynecology, surgery, pediatrics and psychiatry. The book is illustrated throughout with charts, tables, graphs, line drawings and full color photographs to aid in complete comprehension. Passing the USMLE: Clinical Knowledge is a necessary study guide for any student eager to find all the clinical information they need to pass their exam in one handy resource.